Kinetics of Thin Layer Drying of Button Mushroom - Wakchaure, G C; Manikandan, K; Mani, Indra; Shirur, Mahantesh (Journal of Agricultural Engineering, 2010)
Drying kinetics of white button mushroom (Agaricus bisporus) slices in a fluidized bed dryer at three different drying air temperatures of 45, 55 and 65 degree C with constant drying air velocity of 2.5 m.s?¹ was studied. The drying of mushroom slices occurred in the falling rate period. Seven thin-layer drying models, commonly used for perishable fruits/vegetables, were tested for the drying behaviour of mushroom slices. The logarithmic model fitted best to moisture ratio data with higher R² and least c², MBE, RMSE values. The effective moisture diffusivity in white button mushroom increased from 9.21x10?8 to 1.49x10?7 m².s?¹with increasing drying air temperatures in the fluidized bed dryer. The average activation energy of 36.39 kJ.mol?¹ was required for detaching the water molecules from mushroom slices during fluidized bed drying.